Diverse Use of the WEB Device: A Technical Note on WEB Stenting and WEB Coiling of Complex Aneurysms. (1st September 2019) - Roa, Jorge A; Zanaty, Mario; Dandapat, Sudeepta; Samaniego, Edgar; Jabbour, Pascal; Hasan, David M
Abstract: INTRODUCTION: The Woven EndoBridge (WEB) device has recently emerged as an alternative to embolize complex intracranial aneurysms (IAs). However, there are limitations to the WEB device such as inability to secure acutely ruptured and wide-neck IAs. METHODS: We conducted a retrospective analysis of our prospectively collected database of patients with IAs who underwent treatment with WEB device in conjunction with stenting and/or coiling, or WEB device placement in challenging locations. RESULTS: A total of 7 patients/IAs were included. Average age was 59.3 ± 7.8 yr. All patients were women, and 2 presented with SAH. Two patients were treated with simultaneous stenting and WEB placement. One patient had a previous stent through which the WEB was placed. One patient underwent coiling, WEB and stent placement simultaneously. Another patient had a post-coiling recurring aneurysm which was treated with WEB placement. One patient was treated with WEB and coiling. One patient had an ophthalmic artery aneurysm with an acute angle treated with WEB alone. Two patients developed an asymptomatic decrease in flow in the parent vessel, which was successfully restored with the initiation of Tirofiban. One patient developed a herniation of the WEB device through the stent, requiring salvage with an expandable balloon that crushed the WEB against the stent and pushed it back to the aneurysm. No permanent complications or clinical deficits were reported after the endovascular procedures. The occlusion score was as follows: 4/7 cases (57.1%) achieved 100% occlusion, 2/7 cases (28.6%) had neck remnants, and 1 case (14.3%) had an aneurysmal remnant. One patient with severe SAH (Hunt & Hess grade IV) died due to no improvement in neurological exam and withdrawal of care. CONCLUSION: WEB can be safely used in adjunct to coiling and/or stenting, or as a wire-navigation tool. Accurate sizing before deployment is critical.